Monitoring of head injury by myotatic reflex evaluation. Issue 5 (1st May 2000) - Cozens, J Alastair; Miller, Simon; Chambers, Iain R; Mendelow, A David
Abstract : OBJECTIVES: (1) To establish the feasibility of myotatic reflex measurement in patients with head injury. (2) To test the hypothesis that cerebral dysfunction after head injury causes myotatic reflex abnormalities through disordered descending control. These objectives arise from a proposal to use reflex measurements in monitoring patients with head injury. METHODS: The phasic stretch reflex of biceps brachii was elicited by a servo-positioned tendon hammer. Antagonist inhibition was evoked by vibration to the triceps. Using surface EMG, the amplitude of the unconditioned biceps reflex and percentage antagonist inhibition were measured. After standardisation in 16 normal adult subjects, the technique was applied to 36 patients with head injury across the range of severity. Objective (1) was addressed by attempting a measurement on each patient without therapeutic paralysis; three patients were also measured under partial paralysis. Objective (2) was addressed by preceding each of the 36 unparalysed measurements with an assessment of cerebral function using the Glasgow coma scale (GCS); rank correlation was employed to test a null hypothesis that GCS and reflex indices are unrelated. RESULTS: In normal subjects, unconditioned reflex amplitude exhibited a positive skew requiring logarithmic transformation. Antagonist inhibition had a prolonged time course suggesting presynaptic mechanisms; subsequent measurements were standardised at 80 ms conditioning test interval (index termed "TI80 ").  Measurements were obtained on all patients, even under therapeutic paralysis (objective (1)). The unconditioned reflex was absent in most patients with GCS less than 5; otherwise it varied little across the patient group. TI80 fell progressively with lower GCS, although patients' individual GCS could not be inferred from single measurements. Both reflex indices correlated with GCS (p<0.01), thereby dismissing the null hypothesis (objective (2)). CONCLUSION: Cerebral dysfunction in head injury is reflected in myotatic reflex abnormalities which can be measured at the bedside. With greater reproducibility, reflex measurements may assist monitoring of patients with head injury.